“PETITION OF NAIMANOV QUBA” OF 1816 AS A NEW SOURCE ON BIOGRAPHY OF THE DAGESTAN SCHOLAR OF THE SECOND HALF OF THE 18TH CENTURY MUHAMMAD IBN ALI AL-DAGISTANI (KAZAKAY-KADI ALIEV) - Hanmurzaev, Ismail Ibragimovic; Idrisov, Usup Magomedovic (History, Archeology and Ethnography of the Caucasus, 2019)
The article elaborates the biography of a prominent Muslim scholar of the second half of the 18th century Muhammad ibn Ali al-Dagistani. The scholar contributed greatly to the renaissance of traditions of Muslim education, especially to the teaching of the Arabic language in Volga region and Ural. Based on the written source “Petition of Naimanov quba”, introduced by the authors into the scientific community for the first time, it became possible to clarify the information already available about this historical figure. Particularly, analysis of the said document allowed us to identify that the real name of Muhammad ibn Ali al-Dagistani was Kazakay-kadi, the son of Ali (Aliev), and the fact of him owning a son – Magomatjan (Muhammadjan), who also was both a teacher in madrasa and a qadi. The article provides an original version of the reasons for the distortion of the scholar’s name. The scholar’s belonging to the Karanogai quba (kin) Naiman, as well as previously unknown information about the return of his son to his father’s homeland have been revealed. The biography of Kazakay-kadi Aliev is verified by the authors based on a critical comparison of the facts provided in the text, and on fragmentary information contained in the works of Shihab ad-Din Marjani, Rizaitdin Fakhretdinov and Nazir ad-Dorgeli, which allowed to specify the circumstances of his appearance in the Orenburg province and his subsequent relocation to the Kazakh steppe, as well as his role in Russian-Kazakh relations. The reconstruction of the biography of the scholar is supplemented by a list of his most outstanding students. The newly discovered source is of not only historical, but also linguistic interest as a written monument of the North Caucasian Turkic language. The content of the source text is analyzed based on the textological, paleographic and historical-comparative methods of analysis. The document under study contains extensive anthroponymic material that can significantly expand the previously accumulated fund of ancient Nogai proper names.